Densification and Mechanical Properties of sintered Al2O3-Y3Al5O12 ceramic composite - dos Santos, Claudinei; Paneto, Flavio Jose; Pereira, Joaquim Lopes; Oliveira, Jean de Lima; Filho, Edson de Jesus; da Silva, Leandro Anselmo; Lima, Eduardo de Sousa; Cabral, Ricardo de Freitas (Cadernos UniFOA, 2014)
In this work, Al2O3-Y3Al5O12 ceramic composites were developed with different proportions of Al2O3-Y2O3, which were mixed and compacted at different pressures of 40MPa to 100MPa, being consequently sintered at 160°C-2h. The sintered samples were characterized by X-ray diffraction presenting a-Al2O3 and Y3Al5O12 as crystalline phases. Samples with relative densities ranging from 78 to 80% and 87 to 91% were obtained depending on the composition and the compaction pressure used. The hardness values obtained were of 1010 to 1080HV and 370-470HV, for mixes Al2O3-Y2O3 having the composition with levels of 20 and 36.5wt.%, respectively.